An mRNA-based FimH nanoparticle vaccine against uropathogenic Escherichia coli is highly immunogenic in rodents - Roier, Sandro; Adamo, Roberto; Rosini, Roberto; Pezzicoli, Alfredo; Scarselli, Maria; Petsch, Benjamin; Jasny, Edith; Rauch, Susanne (Frontiers in Immunology, 2025)
BackgroundUropathogenic Escherichia coli (UPEC) is the leading cause of urinary tract infections (UTIs), which are increasingly antibiotic resistant and frequently recur. Novel therapeutics are sought to treat and prevent recurrent UTIs (rUTIs), including vaccines. Key virulence factor FimH, which mediates bacterial adhesion to host cells and biofilm formation, is a promising target for a vaccine against UPEC. We assessed the immunogenicity of mRNA-based nanoparticle vaccines against UPEC containing FimH as the encoded antigen.MethodsLipid nanoparticle (LNP)-formulated mRNA vaccines encoding FimH as a monomeric, pre-binding conformation protein (FimHDG), or a multimeric protein nanoparticle (PNP) through fusion to Helicobacter pylori ferritin (FimHDG-Ferritin) were developed. Immunogenicity was assessed in vivo in female BALB/cAnNRj mice and female Wistar rats following three intramuscular (IM) injections of FimHDG or FimHDG–Ferritin mRNA vaccines, or comparator protein subunit vaccines. Antibody levels and functional response were measured in serum and urine by ELISA and bacterial adhesion inhibition (BAI) assays. T cell response was characterized by flow cytometry.ResultsIn both animal models, unmodified FimHDG and FimHDG-Ferritin mRNA vaccines induced higher functional serum antibody levels compared with the protein subunit vaccine control, at the tested dosages. FimHDG-Ferritin resulted in greater binding antibody levels and higher splenic FimH-specific CD4+ and CD8+ T cell responses compared with monomeric FimHDG in both models, resulting in its nomination as lead candidate vaccine design. Validation in rats demonstrated that N1mΨ nucleoside modification further enhanced FimHDG-Ferritin immunogenicity compared with unmodified mRNA.ConclusionsThe mRNA vaccine FimHDG-Ferritin with N1mΨ-modified nucleosides is a promising candidate for further development as a vaccine against UPEC.